2014
DOI: 10.3354/sedao00005
|View full text |Cite
|
Sign up to set email alerts
|

Maturity of the pufferfish Lagocephalus sceleratus in the southeastern Mediterranean Sea

Abstract: The present study assesses maturity and reproductive dynamics of pufferfish Lagocephalus sceleratus (Gmelin, 1789) off Cyprus (southeastern Mediterranean Sea), in relation to regional differences in oceanographic conditions, habitat characteristics and fishing activity. In addition, the allometric pattern of gonadal growth was studied to validate the use of the gonadosomatic index (GSI) in assessments of the reproductive cycle. To do so, 4743 pufferfish were sampled between May and October 2010 so as to cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 31 publications
5
34
0
Order By: Relevance
“…Also Rousou et al (2014) reported that, the reproductive season of L. sceleratus off Cyprus was found to extend from late spring to middle summer.…”
Section: Seasonal Variations In Maturity Stagesmentioning
confidence: 95%
See 1 more Smart Citation
“…Also Rousou et al (2014) reported that, the reproductive season of L. sceleratus off Cyprus was found to extend from late spring to middle summer.…”
Section: Seasonal Variations In Maturity Stagesmentioning
confidence: 95%
“…3 and 4). The Mediterranean population attains L population, may be related to the favorable conditions, food availability in such area of sub-tropical to temperate zones especially this species itself well along the different coasts of Mediterranean basin according to their ability as a member of open water hunters (Kalogirou, 2013;Farrag, 2014 andRousou 2014). …”
Section: -Sex Ratiomentioning
confidence: 99%
“…L. sceleratus was first reported in the Mediterranean Sea in February 2003 at Gökova Bay (southern Aegean Sea, Turkey) (Akyol et al, 2005), in November 2004 at Jaffa along the Israeli coast (Golani and Levy, 2005), and in July 2005 in the Cretan Sea, Greece (Kasapidis et al, 2007). Since then, L. sceleratus has been recorded with increasing frequency in Greece, Cyprus, Malta, Algeria, and Turkey and is considered as one of the fastest expanding Lessepsian invaders (Acar et al, 2017;Deidun et al, 2015;Kara et al, 2015;Katikou et al, 2009;Kosker et al, 2016;Rodriguez et al, 2012;Rousou et al, 2014). In Spain, one individual of L. sceleratus was captured in July 2014 in Denia (Alicante, Western Mediterranean) (Katsanevakis et al, 2014) and is the object of the present publication.…”
Section: Introductionmentioning
confidence: 99%
“…It eats economically important cephalopods Sepia officinalis and Octopus vulgaris (Cuvier 1797) and is classed as a fisheries pest (Kalogirou 2013). Some countries have initiated invasive fish eradication programmes, for example the Cypriot authorities have been compensating fishermen for their pufferfish catches during the reproductive season, resulting in massive removals of pufferfish biomass from the eastern Mediterranean (Rousou et al 2014).…”
Section: Introductionmentioning
confidence: 99%